2019
DOI: 10.1186/s12898-019-0244-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of Antarctic shallow soft-bottom benthic communities: ecological drivers under climate change

Abstract: Background Marine soft sediments are some of the most widespread habitats in the ocean, playing a vital role in global carbon cycling, but are amongst the least studied with regard to species composition and ecosystem functioning. This is particularly true of the Polar Regions, which are currently undergoing rapid climate change, the impacts of which are poorly understood. Compared to other latitudes, Polar sediment habitats also experience additional environmental drivers of strong seasonality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…A notable result is that metabarcoding in the majority of cases outperformed morphotaxonomy concerning the number of taxa retrieved (see e.g. Cowart et al 2015;Lobo et al 2017;Vause et al 2019). DNA metabarcoding in seagrass sediment samples for example yielded hundreds to thousands of MOTUs (molecular operational taxonomic units) compared to only 323 species morphologically identified (Cowart et al, 2015).…”
Section: Current Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable result is that metabarcoding in the majority of cases outperformed morphotaxonomy concerning the number of taxa retrieved (see e.g. Cowart et al 2015;Lobo et al 2017;Vause et al 2019). DNA metabarcoding in seagrass sediment samples for example yielded hundreds to thousands of MOTUs (molecular operational taxonomic units) compared to only 323 species morphologically identified (Cowart et al, 2015).…”
Section: Current Limitationsmentioning
confidence: 99%
“…DNA metabarcoding in seagrass sediment samples for example yielded hundreds to thousands of MOTUs (molecular operational taxonomic units) compared to only 323 species morphologically identified (Cowart et al, 2015). Likewise, Vause et al (2019) found 62 orders in sediment samples from Antarctica with metabarcoding compared to 37 orders based on morphology. Similar results were found for plankton communities (Abad et al, 2016;Deagle et al, 2018) and hard substrate samples (Pearman et al, 2016).…”
Section: Current Limitationsmentioning
confidence: 99%
“…However, the geographic, functional, and taxonomic generality of latitudinal diversity gradients remain lively debated as unimodal, bimodal, and inverse gradients emerge across clades, habitats, and latitudes ( Rivadeneira et al, 2002 ; Waller, 2008 ; Chaudhary et al, 2016 ; Kinlock et al, 2018 ). In the marine realm, latitudinal gradients in some groups have been shown to be closely related to oceanographic covariates, such as water temperature ( Roy et al, 2000 ), yet mammal richness peaks at high latitudes ( Grady et al, 2019 ), and more species have been reported from polar soft-sediment habitats than at many lower latitudes ( Vause et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the marine realm, latitudinal gradients in some groups have been shown to be closely related to oceanographic covariates, such as water temperature (Roy et al, 2000), yet mammal richness peaks at high latitudes (Grady et al, 2019), and more species have been reported from polar soft-sediment habitats than at many lower latitudes (Vause et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the geographic, functional and taxonomic generality of latitudinal diversity gradients remain lively debated as unimodal, bimodal and inverse gradients emerge across clades, habitats and latitudes [6][7][8][9]. In the marine realm, latitudinal gradients in some groups have been shown to be closely related to oceanographic covariates, such as water temperature [10], yet mammal richness peaks at high latitudes [11], and more species are found in polar soft-sediment habitats than at many lower latitudes [12].…”
Section: Introductionmentioning
confidence: 99%